I'll scream later - Matlin, Marlee, 1965-; Sharkey, Betsy (New York : Simon Spotlight Entertainment, 2009)
The compelling memoir of the Academy Award-winning actress and role model for 30 million deaf and hard-of-hearing people serves as an inspiration and a lesson in overcoming adversity.
Keywords: Matlin, Marlee, -- 1965-.; Actors -- United States -- Biography; Authors, American -- 21st century -- Biography; Deaf -- United States -- Biography; KVHA:American Studies; KVHA:Cultuurgeschiedenis; Amerikaanse Gebarentaal; KVHA:Film; Amerikaanse Gebarentaal